Psychedelic prophets : the letters of Aldous Huxley and Humphry Osmond - Bisbee, Cynthia Carson (McGill-Queen's/Associated Medical Services studies in the history of medicine, health, and society, 2018)
Letters between the men who coined the term ""psychedelic"" and opened doors to a different way of thinking about human consciousness.